Avian Influenza Viruses, Inflammation, and CD8+ T Cell Immunity - Wang, Zhongfang; Loh, Liyen; Kedzierski, Lukasz; Kedzierska, Katherine (Frontiers in Immunology, 2016)
Avian influenza viruses (AIVs) circulate naturally in wild aquatic birds, infect domestic poultry and are capable of causing sporadic bird-to-human transmissions. AIVs capable of infecting humans include a highly pathogenic AIV H5N1, first detected in humans in 1997, and a low pathogenic AIV H7N9, reported in humans in 2013. Both H5N1 and H7N9 cause severe influenza disease in humans, manifested by acute respiratory syndrome distress syndrome, multi-organ failure and high mortality rates of 60% and 35%, respectively. Ongoing circulation of H5N1 and H7N9 viruses in wild birds and poultry, and their ability to infect humans emphasizes their epidemic and pandemic potential and poses a public health threat. It is, thus, imperative to understand the host immune responses to the AIVs so we can control severe influenza disease caused by H5N1 or H7N9 and rationally design new immunotherapies and vaccines. This review summarises our current knowledge on AIV epidemiology, disease symptoms, inflammatory processes underlying the AIV infection in humans and recent studies on universal pre-existing CD8+ T cell immunity to avian influenza viruses. Immune responses driving the host recovery from AIV infection in patients hospitalized with severe influenza disease are also discussed.